The Description of Nurses Knowledge Level About Healthcare Associated Infections (HAIs) at dr. Soehadi Regional Hospital Prijonegoro Sragen - Mabrurah, Farida; Hermawati (Al-Hijrah Indonesia, 2023)
The incidence of Healthcare Associated Infections (HAIs) in Indonesia is higher than in developed countries, in Indonesia it is 15.74% while in developed countries it is only 4.8-15.5%. In the Sragen district, the highest HAIs were in dr. Soehadi Regional Hospital Prijonegoro Sragen with 9.1%. The most common cause of HAIs is because nurses do not comply with hand hygiene. Nurses knowledge level about HAIs must be increased to reduce the incidence rate. to determine the characteristics and description of nurses’ knowledge level about Healthcare Associated Infections (HAIs) at dr. Soehadi Regional Hospital Prijonegoro Sragen. This study used a questionnaire measuring instrument, this research method is descriptive analysis with sampling using a random sampling technique with a total sample of 73 respondents. The results showed the characteristics of the majority of nurses aged 41-55 years, female, Bachelor of Nursing education, and description of the nurses’ knowledge level about Healthcare Associated Infections (HAIs) at dr. Soehadi Regional Hospital Prijonegoro Sragen is in the high category (87.7%). Nurses’ knowledge level about Healthcare Associated Infections (HAIs) at dr. Soehadi Regional Hospital Prijonegoro Sragen in the high category.